The Key to Pro-Business Public Services Success: An Analysis of Motivation and Job Satisfaction - Melanda Wulandari; Asep Jamaludin; Nandang Nandang (Lembaga Riset dan Inovasi Al-Matani, 2025)
This study aims to examine the influence of motivation and job satisfaction on employee performance at the One-Stop Investment and Integrated Services Office (DPMPTSP). The research employs a quantitative method with a survey approach. The sample consists of the entire population of employees at DPMPTSP, totaling 50 individuals. Primary data were collected through questionnaires. The data were analyzed using multiple regression with the assistance of SPSS version 26.0. The results indicate that employee motivation at DPMPTSP falls under the